Identifikasi Bryophyta di Kawasan Taman Hutan Raya Ir. H. Djuanda - Silmi Aulia Putri; Silmi Mawarni; Ateng Supriatna (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is considered one of the 17 megadiverse countries. The second biggest group of plants is moss. Indonesia approximately has a wide variety of moss. The method we used is explorative study and documentation that aimed to identify moss species at Djuanda Forest Park. Identify processed guided by identification book named Mengenal Tumbuhan Lumut (Bryophyta) Deskripsi, Klasifikasi, Potensi, dan Cara mempelajarinya oleh Marheny Lukitasari (2018). As A result, we identified 10 species of moss at Djuanda Forest Park.